Pottery craft of the Yakut - Savvin, Andrej A. 1896-1951 (Academica Press, 2023)
This book offered to the reader's attention is an ethnographic study devoted to the traditional pottery of Yakutia. The author, A. A. Savvin, collected materials for the book during field research in 1939?1941, when ceramic tableware had largely already lost its former role in the household way of the Yakuts. But the skills for its manufacture were still preserved in certain localities. Savvin managed to document the last "living" evidence of a craft that had a centuries-old history and established traditions. It is noteworthy that the research conducted by Savvin was a scientific project in the modern sense of the term. It was carefully planned and executed in accordance with a pre-written program, which is also included in this edition. The sources of information were not only direct observations of the working processes of the production of ceramic tableware but also conversations-interviews with potters, memoirs of representatives of the older generation. A special layer of research consisted of materials of folklore, folk beliefs, and customs related to pottery.00Transl. by Richard L. Bland